Employee Value Proposition and Total Rewards: Tools of the Trade in Today’s Competitive Market - Binghay, Virgel C. (Philippine Journal of Labor and Industrial Relations, 2025)
In today’s highly competitive market, an ongoing “war on talent” has emerged: companies are neck and neck to attract, engage and retain the best talent. Corporate culture has changed as well due largely to the generational shift brought by millennials to the contemporary workplace. Employees now seek growth and career development and not necessarily the womb-to-tomb paternalistic relationship of the past. Two important tools and techniques emerge in human resource (HR) management: employee value proposition (EVP) and total rewards (TR). Both put a premium on a more holistic approach in the employer-employee relationship, going beyond mere compensation and financial remuneration that are considered the employment deal. While the terms are very similar, they are not entirely synonymous. This paper seeks to differentiate the two and at the same time provide a point of convergence as to how both can be employed to better manage an organization’s HR. Discussions include presentation of cases from select Philippine-based companies that show the complementarity of these tools.